Romantic Prophecy and the Resistance to Historicism - Bundock, Christopher (Book collections on Project MUSE., 2016)
In this remarkably erudite work, Christopher Bundock argues that the repeated failure of prophecy in Romantic thought is creative and enables a renewable potential for expression across disciplines.